Challenges of public-private partnership model in public hospitals in Yazd - Moslem Mohsenbeigi; Mohamad Zarezade; KHadije Nasiiani; Mohamad Ranjbar; Mohammad Reza Vafaeenasab (Tehran University of Medical Sciences, 2022)
Introduction: Despite many challenges, public-private partnership in hospitals is recognized as one of the most attractive investment platforms for the private sector. This study conducted to assess the challenges of private sector partnership with public hospitals using the public-private partnership model in public hospitals in Yazd. Methods: The present qualitative research conducted in 2021. The viewpoints of 15 faculty members, directors, managers and operational experts on the participation of the private sector, those related to the transfer and contracts and the parties of the private sector are extracted through a semi-structured interview guide and analyzed using content analysis in three stages. Results: A total of 10 main themes including economic and policymaking problems, insufficient manpower readiness, lack of support authority, weak partnership laws, lack of knowledge and experience of managers in partnership, lack of financial transparency, conflict of interest, poor coordination, lack of cultural readiness and trust-building and lack of plans and supervision in the field of partnership in 28 sub-themes extracted. Conclusion: There are challenges related to policymaking issues and the resulting instability, incoordination of different units, unpreparedness of manpower and contract details in using different models of public-private partnership in hospitals, in which the use of the same procedures, transparency and the meeting requirements of the private sector are recommended for partnership and the formulation of laws and contracts free from any shortcomings and weaknesses that could lead to the loss of the public sector.